The Nation Form in the Global Age Ethnographic Perspectives - Ahmad, Irfan; Kang, Jie (Global Diversities,, 2022)
These incisive essays explore nationalist violence and ethno-religious purification in Europe, South Africa, the Middle East, India, and China. Readers will encounter the extreme precarity of Islamic minorities and migrants, as well as inspiring explorations of alternative imaginaries beyond the nation form. Kenneth Dean, Professor, National University of Singapore. This excellent edited volume is a tribute to a major anthropologist of our times that combines approaches based on comparison with an analytic attention to circulation, thus showing us that the nation-form dominates our world because of its viral capacity to find hosts in highly variable cultural, religious and political contexts, which it then pushes in the direction of xenophobia, exclusion and populism. Arjun Appadurai, Max Weber Global Professor, Bard Graduate Center, New York, USA This collection of global ethnographies makes evident that the global expansion of the nation is as intrinsic to processes of globalization as the global expansion of capitalist markets. It also shows that in our global age religion and its binary secular remain inextricably intertwined with both dynamics of globalization. José Casanova, Emeritus Professor, Georgetown University, USA This open access book argues that contrary to dominant approaches that view nationalism as unaffected by globalization or globalization undermining the nation-state, the contemporary world is actually marked by globalization of the nation form. Based on fieldwork in Africa, Asia, Europe and the Middle East and drawing, among others, on Peter van der Veer's comparative work on religion and nation, it discuss practices of nationalism visa-a-vis migration, rituals of sacrifice and prayer, music, media, e-commerce, Islamophobia, bare life, secularism, literature and atheism. The volume offers new understandings of nationalism in a broader perspective. Irfan Ahmad is Senior Research Fellow at the Max Planck Institute for the Study of Religious and Ethnic Diversity, Germany. Jie Kang is Research Fellow and Project Coordinator at Max Planck Institute for the Study of Religious and Ethnic Diversity, Germany.